Effectiveness of Intrathecal Morphine for Analgesia following Elective Caesarean Section - Koju, RB; Gurung, BS; Dongol, Y (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study evaluates the effectiveness of usage of 0.2 mg intrathecal morphine as post-operative analgesia and its effect on activity of mother after elective cesarean section. Methods: This hospital based prospective, randomized, double-blinded and placebo controlled study was carried out at Nagarik Community Teaching Hospital, Bhaktapur between 2012 January to 2014 November after the approval was taken from the hospital authority and the written informed consent from the participating patients. Fifty women of ASA I or II physical status undergoing cesarean section under sub-arachnoid block was randomized into two groups – P group (placebo group, n = 25) and M group (Treatment group, n = 25). P Group received hyperbaric bupivacaine 2.3ml, 0.5% bupivacaine (11.5 mg) and M Group received morphine 0.2 ml (0.2 mg) plus bupivacaine 2.3ml, 0.5% (11.5 mg) intrathecally. All subjects received 8 mg ondansetron intravenously 30 minutes before surgery to prevent possible drug-induced pruritus and post-operative nausea and vomiting. 1000 mg rectal acetaminophen suppository was given at the end of the surgery. Pain, nausea and pruritus during the first 24 hours using visual analog scale were recorded by a trained nurse or attending doctor who was not involved in the study. Results: Duration of complete analgesia and the time to request for additional analgesics was longer in M Group than in P Group. Similarly, the active movement is earlier in M Group than in P Group. There were no significant differences in adverse effects between the groups. Conclusions: Addition of morphine 0.2 mg to heavy bupivacaine intrathecally reduced post-operative pain and analgesic requirements without any significant difference in adverse effects.